Perancangan Gedung Auditorium Universitas Nahdlatul Ulama Gorontalo dengan Konsep Regionalisme - Fajar Yuliano Ishak; M Fauzhan Algiffari; Frans Mitran Ajami (Politeknik Kebangsaan, 2026)
The development of higher education infrastructure, especially auditorium buildings, is now required not only to be functional and modern but also to reflect local identity as a form of responsibility toward local culture and environment. Universitas Nahdlatul Ulama Gorontalo (UNUGO), as an educational institution based on Islamic values and local culture, requires a representative academic support facility. This study aims to design an auditorium building for UNUGO using an architectural regionalism approach, integrating functional aspects with the unique cultural, climatic, and local architectural context. This approach accommodates local elements—such as form, materials, and cultural symbolism—into a modern architectural design. The proposed design is expected to strengthen the campus's identity, support academic activities, and enrich the treasury of contextual and sustainable local architecture. The design of the UNUGO auditorium represents: 1) an inclusive deliberative space; 2) sustainable yet adaptive cultural symbols; 3) a climate- and human-friendly architecture; 4) a spiritual and intellectual hub; and 5) a harmonious blend of tradition and modernity. This building is expected to become a campus architectural icon that not only accommodates activities but also conveys the narrative of the identity, values, and local spirit of the Gorontalo community within the framework of Nusantara Islam. Thus, the UNUGO auditorium will be a manifestation of contextual, sustainable, and meaningful architecture.